Impact of Cross-Cultural Internship Experience on International Students’ Psychological Stress and Adaptability - Wu, Tzu-Ying; Thongma, Weerapon; Tsai, Chin-Fa; Leelapattana, Winitra (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Cross-cultural internships have become increasingly popular among international students, offering valuable opportunities for personal and professional growth. However, the challenges associated with adapting to a new cultural environment can lead to psychological stress, affecting students’ overall well-being and internship performance. This study aims to investigate the impact of cross-cultural internship experiences on international students’ psychological stress and adaptability and to identify strategies for managing stress and enhancing adaptability. Materials and Methods: A mixed-methods approach was used, combining surveys and semi-structured interviews with 300 international students who completed cross-cultural internships. Participants were selected through purposive sampling for diverse perspectives based on nationality, language ability, and cultural distance, which is vital for the study’s reliability. Quantitative data measured psychological stress and adaptability, while qualitative data explored challenges, coping strategies, and personal growth. Statistical and thematic analyses examined the relationship between internship experiences and psychological outcomes. Results: The study revealed that cross-cultural internships had a significant impact on international students’ psychological stress and adaptability. Quantitative findings indicated a positive correlation between the duration and intensity of cultural exposure and levels of stress and adaptability. Qualitative themes emerged, highlighting common challenges such as language barriers, cultural differences, and work-related pressures. Effective coping strategies, including seeking social support, engaging in self-reflection, and developing cultural competence, were identified. Participants also reported personal growth outcomes, such as increased resilience, self-awareness, and intercultural communication skills. Conclusion: Cross-cultural internships present challenges and opportunities for international students’ psychological well-being and adaptability. The findings underscore the importance of providing targeted support and resources, such as a mentor or homeroom teacher and staff, to help students manage stress and enhance their adaptability in cross-cultural settings. Educational institutions and host organizations should collaborate to develop pre-departure training, on-site mentoring, and re-entry support programs. Further research should examine the long-term effects of cross-cultural internships on career trajectories.